Na+/K+-ATPase regulates the K+/Na+ homeostasis in the intertidal macroalgae, Neoporphyra haitanensis, in response to salt stress - Chen, Qi; Xu, Kai; Xu, Yan; Ji, Dehua; Chen, Changsheng; Xie, Chaotian; Wang, Wenlei (Frontiers in Plant Science, 2023)
In plants under hypersaline stress, the main transporter that extrudes sodium ions (Na+) is the Na+/H+ antiporter SOS1. Different from land plants, the intertidal macroalgae, Neopyropia/Neoporphyra contains an animal-type Na+/K+-ATPase as well as the SOS1 system. However, the contribution of Na+/K+-ATPase to the K+/Na+ homeostasis of intertidal macroalgae remains unclear. In this study, we analyzed the function of Na+/K+-ATPase in the response of Neoporphyra haitanensis to salt stress from the perspective of ion transport dynamics. Both the transcript level of NhNKA2 and enzyme activity of Na+/K+-ATPase increased in the early response of N. haitanensis thalli to hypersaline stress. Addition of ouabain, an inhibitor of Na+/K+-ATPase, resulted in Na+ accumulation in the cells, severe K+ leakage from the thalli, and then remarkably disturbed the K+/Na+ homeostasis in N. haitanensis thalli. This disruption might induce a significant decrease in photosynthesis and a severe oxidative damage in thalli. Accordingly, these results suggested that the important role of Na+/K+-ATPase in the resistance of intertidal macroalgae to hypersaline stress, and shed light on the diversity of K+/Na+ homeostasis maintenance mechanisms in plants.